2000
DOI: 10.1034/j.1600-0404.2000.102002087.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after first cerebral infarction in young adults

Abstract: Our data suggest that recurrence of stroke is a major clinical problem also for the patients aged less than 45 years and that it might be more frequent with specific clinical syndromes and etiologic subtypes of first stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…Furthermore, the low prevalence of migraine and the lack of characterization of migraine subtypes in some of the previous studies prompt the speculation that several possible biases in the assessment of individual migraine history were also operant. [28][29][30][31][32][33][34][35] As an indirect support to our findings, Gioia and coworkers 36 recently found a higher prevalence of MA in young patients with stroke with silent ischemic lesions on brain MRI, an independent predictor of recurrence, in comparison with those with no evidence of brain abnormalities. This reinforces the hypothesis that MA might also predict clinical recurrent events.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, the low prevalence of migraine and the lack of characterization of migraine subtypes in some of the previous studies prompt the speculation that several possible biases in the assessment of individual migraine history were also operant. [28][29][30][31][32][33][34][35] As an indirect support to our findings, Gioia and coworkers 36 recently found a higher prevalence of MA in young patients with stroke with silent ischemic lesions on brain MRI, an independent predictor of recurrence, in comparison with those with no evidence of brain abnormalities. This reinforces the hypothesis that MA might also predict clinical recurrent events.…”
Section: Discussionsupporting
confidence: 73%
“…This is not surprising when considering the well-known prothrombotic effects of these molecules, and it is even more likely if we take into account the controversy on the most adequate treatment approach in these cases. 30,40 The assessment of factors we identified as predictors of arterial thrombotic recurrence is part of the routine clinical investigation of patients with ischemic stroke at a young age. Therefore, the risk score we developed based on such factors is a simple prediction algorithm for the estimation of the individual long-term risk in this age category in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke in the young originates limitations in the quality of life and occupational status [9,12,20,21,40,44]. Series have reported that between 50%-70% of young adults with stroke return to work, with a time period ranging from several days after stroke to 40 months, with a mean of 8 months.…”
Section: Occupational Statusmentioning
confidence: 99%
“…Thus, prognosis of stroke in young as a whole has been described as favorable in most of the series [12,[17][18][19][20][21], but the long-term prognosis is notably worse when compared with the general population of the same age, with higher death rate, higher risk of cardiovascular events, and significant limitations in quality of life [12]. Moreover, in our series (with a mean followup of almost 12 years and mean age of 36 years old), only 57% of the patients followed for more than 3 years are alive, free of significant disability, stroke recurrence or other vascular event [12].…”
Section: Introductionmentioning
confidence: 99%
“…In studies evaluating stroke in young patients, a relatively low rate of annual recurrence of between 1.4 and 2.6% has been found [16,17,18,19]. However, stroke in the young carries an excess mortality compared to those of the same age in the general population [19] and its repercussion in terms of years-of-life-lost and/or economic costs due to resultant disabilities are of great importance.…”
Section: Recurrence and Agementioning
confidence: 99%